2016
DOI: 10.4236/jbise.2016.910041
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Somatic Cervical Pain and Disability after the Application of a Portable TENS Device

Abstract: Background: Cervical facet joints and neck muscles are common nociceptive pain generator, with neck and shoulder muscles pain, and limited retroflexion. Objective: To test the hypothesis that the portable TENS device would relieve cervical somatic pain. Methods: Forty-four patients with chronic cervical pain patients with somatic pain, but without radicular symptoms were evaluated in a double-blind, prospective, randomized fashion, divided into sham and active groups. The active TENS (TANYX ) or sham device w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…More severe side effects include angioedema, increased anticoagulant effects, and serotonin toxicity (21) . Lauretti et al (22) demonstrated in a study with 44 patients with cervical pain that there was a reduction in analgesics with the introduction of TENS to control pain, also demonstrating an improvement in comfort and well-being after using this technology.…”
Section: Discussionmentioning
confidence: 99%
“…More severe side effects include angioedema, increased anticoagulant effects, and serotonin toxicity (21) . Lauretti et al (22) demonstrated in a study with 44 patients with cervical pain that there was a reduction in analgesics with the introduction of TENS to control pain, also demonstrating an improvement in comfort and well-being after using this technology.…”
Section: Discussionmentioning
confidence: 99%